METHODOLOGICAL FUNDAMENTALS OF STUDENTS' LEARNING ACTIVITIES (Pedagogy of Higher and Secondary Education, 2022)
The article explains of principles and ways of organizing learning activities of students, revealed the advantage of a systematic approach to the educational proach.
Keywords: education activities; the methodology; system; systematic approach